PENANGANAN KEPADATAN DAN KEKUMUHAN PERMUKIMAN BANTARAN SUNGAI KAHAYAN KECAMATAN PAHANDUT KOTA PALANGKA RAYA: Handling Density and Slum Settlements in the Kahayan Riverbank Area, Pahandut District, Palangka Raya City - Martono, Martono (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2026)
High population growth in Pahandut District, Palangka Raya City, has created significant pressure on urban housing demand. The limited availability of affordable residential land, particularly for low-income communities, has driven the use of informal spaces, including the Kahayan Riverbank area. The river buffer zone, which should function as an ecological protection area, has developed into a densely populated settlement with low-quality infrastructure, resulting in slum conditions, environmental degradation, and increased risks of flooding and public health problem. This issue is multidimensional, encompassing demographic, spatial planning, socio-economic, and environmental aspects. This policy paper aims to analyze the factors contributing to density and slum conditions along the Kahayan Riverbank and to formulate effective and sustainable policy alternatives. The method used is descriptive-qualitative policy analysis with a comparative approach to several policy alternatives, namely spatial planning enforcement and relocation, slum upgrading, the provision of affordable housing, and integrated riverbank management based on the Waterfront City concept. The analysis indicates that partial approaches are insufficient to comprehensively address the root causes of the problem. The most relevant policy alternative is integrated riverbank management based on the Waterfront City concept, which combines selective relocation, the provision of affordable vertical housing, ecological revitalization of the river buffer zone, and river-based local economic development. This approach is considered capable of reducing density and slum conditions while simultaneously improving environmental quality and enhancing the area’s competitiveness. This policy is expected to transform the Kahayan Riverbank from a slum area into a productive and sustainable public space, while supporting the realization of an orderly and competitive spatial structure for Palangka Raya City.